Commons-based peer production and artistic expression: Two cases from Greece. (May 2015) - Kostakis, Vasilis; Drechsler, Wolfgang
This essay narrates, from a creator-observation perspective, the production of two works of fiction, a book of short stories and a play, based on the principles and technologies of Commons-based peer production. This is potentially interesting from both the Commons-based peer production and the literary perspective. Even though both seem well-matched by their prima facie lack of profit orientation, Commons-based peer production case studies rarely deal with fiction, and regarding plays, artistic creativity is still mostly associated with one, maybe two authors. After tracing and analysing the Commons-based peer production phenomenon, the case studies show concretely the fate of the specific projects as well as how, nowadays, people can get involved in collaborative artistic projects inspired and catalysed by Commons-oriented principles and technologies.